Late-Onset Sjögren disease: A different clinical entity? - Cengiz, Celil Barlas; Kahraman Denizhan, Tuğba; Kaplan, Hüseyin; Oğuz Kökoğlu, Emel; Kızıltepe, Melih; Eren Cengiz, Burcu; Oğuz, Hanife; Şenel, Abdurrahman Soner (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: Sjögren’s disease(SjD) exhibits heterogeneous clinical phenotypes influenced by age at onset. This study aimed to evaluate the impact of onset age on the clinical and serological characteristics of SjD in a Turkish cohort. Methods: We retrospectively analyzed 411 patients diagnosed with SjD between 2013 and 2024, fulfilling the 2002 AECG or 2016 ACR/EULAR criteria. Patients were classified as young-onset (<40 years; YoSjD), adult-onset (40–60 years; AoSjD), or elderly-onset (>60 years; EoSjD). Demographic, clinical, laboratory, and treatment characteristics were compared among groups. Results: The cohort comprised predominantly females (93.4%) with a median age of 55 years. RF positivity was significantly higher in EoSjS (35.5%) compared to YoSjD (27.9%) and AoSjD (19.2%, p=0.007). Inflammatory markers (ESR, CRP) were more frequently elevated in EoSjD. Interstitial lung disease (ILD) prevalence was highest in EoSjD (25.8%, p<0.05), particularly in males. Artropathy was more frequent in EoSjD (80.6%) and YoSjD (76%) than in AoSjD (64.5%, p=0.007). Anemia was more common in EoSjD (20.4%, p=0.040). Hydroxychloroquine was widely used (86.6%), with glucocorticoid and azathioprine use significantly higher in EoSjD. Conclusions: Elderly-onset SjD demonstrates a distinct phenotype characterized by higher ILD prevalence, increased RF positivity, greater inflammatory activity, and more frequent artropathy and anemia compared to younger-onset groups. These findings highlight the need for age-tailored diagnostic vigilance, proactive ILD screening, and cautious use of immunosuppressants in older patients. Prospective multicenter studies are warranted to refine management strategies in this subgroup.